ChemInform Abstract: Unexpectedly Complex Crystalline Phases in the MSO3F—Ag(SO3F)2 Phase Diagram (M: Na, K, Rb, Cs). Issue 12 (March 2015) - Michalowski, T.; Mazej, Z.; Budzianowski, A.; Jaglicic, Z.; Leszczynski, P. J.; Grochala, W.
Abstract Crystalline phases obtained by reactions of MSO3F (M: Na, K, Rb, Cs), AgSO3F, and (SO3F)2 (77 K → room temp., 2—5 d) are characterized by powder XRD, Raman spectroscopy, and magnetic measurements.